Immuno-metabolic interfaces in cardiac disease and failure. Issue 1 (4th February 2021) - Bertero, Edoardo; Dudek, Jan; Cochain, Clement; Delgobo, Murilo; Ramos, Gustavo; Gerull, Brenda; Higuchi, Takahiro; Vaeth, Martin; Zernecke, Alma; Frantz, Stefan; Hofmann, Ulrich; Maack, Christoph
Abstract: The interplay between the cardiovascular system, metabolism, and inflammation plays a central role in the pathophysiology of a wide spectrum of cardiovascular diseases, including heart failure. Here, we provide an overview of the fundamental aspects of the interrelation between inflammation and metabolism, ranging from the role of metabolism in immune cell function to the processes how inflammation modulates systemic and cardiac metabolism. Furthermore, we discuss how disruption of this immuno-metabolic interface is involved in the development and progression of cardiovascular disease, with a special focus on heart failure. Finally, we present new technologies and therapeutic approaches that have recently emerged and hold promise for the future of cardiovascular medicine.